(untitled) (Iranian Journal of Kidney Diseases, 2017)
Introduction. Chronic kidney disease is a public health problem worldwide that is highly associated with psychological disorders. This study aimed to assess prevalence of depression in hemodialysis patients in Iran. Materials and Methods. Relevant studies were identified from the PubMed, ISI Web of Science, Ovid, Scopus, EMBase, and Iranian databases including Magiran, SID, IranMedex, and Irandoc, up to December 2015. The DerSimonian-Laird random effects model was employed to estimate the overall pooled prevalence. Heterogeneity was investigated and subgroup analyses were carried out by sample size and time of study. Results. Twenty-seven studies on 2822 patients met the inclusion criteria for analysis. The pooled analysis of depressive symptoms in hemodialysis patients in Iran was estimated to be 62% (95% confidence interval, 0.54 to 0.71) with a maximum rate of 95% (95% confidence interval, 0.88 to 1.02) and a minimum rate of 9% (95% confidence interval, 0.02 to 0.16). Statistical heterogeneity was high (I2 = 96.9%). Conclusions. The results of this study showed that depression is common among dialysis patients in Iran. Early diagnosis and effective treatment of depression can improve quality of life, prognosis, and survival of patients.